PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL KOOPERATIF TIPE JIGSAW - FEBRIYENTI, NENENG (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This experiment based on the reality in the elementary school whis is learn dominated by teacher and used conventional method commonly as learning model. The purpose of this experiment to describe the increasing PKn subject by using cooperative model of Jigsaw type around planing, doing and learning result. The approach that used is kualitative and kuantitative with containts of 4 steps that are planing, doing, monitoring and practicing. The experiment subject is fourth grade students of elementary school at  SDN 06 Pasaman Kab. Pasaman Barat. From analysis data can be resulted that cooperative model of Jigsaw type can increase students marks in studying.   Kata kunci : hasil belajar ; pembelajaran PKn ; kooperatif tipe jigsaw